The Martyrdom of Abolitionist Charles Torrey - Torrey, E. Fuller (Edwin Fuller), 1937- (Book collections on Project MUSE., 2013)
During his brief yet remarkable career, abolitionist Charles Torrey -- called the ""father of the Underground Railroad"" by his peers -- assisted almost four hundred slaves in gaining their freedom. A Yale graduate and an ordained minister, Torrey set up a well-organized route for escaped slaves traveling from Washington and Baltimore to Philadelphia and Albany. Arrested in Baltimore in 1844 for his activities, Torrey spent two years in prison before he succumbed to tuberculosis. By then, other abolitionists widely recognized and celebrated Torrey's exploits: running wagonloads of slaves north.